A multilevel puzzle: Migrants' voting rights in national and local elections. (19th October 2016) - ARRIGHI, JEAN‐THOMAS; BAUBÖCK, RAINER
Abstract: How does international migration impact the composition of the demos ? Constitutional doctrines and democratic theories suggest contrasting responses: an insular one excludes both non‐citizen immigrants and citizen‐emigrants; a deterritorialised one includes all citizens wherever they reside; a postnational one includes all residents and only these. This article argues that none of these predicted responses represents the dominant pattern of democratic adaptation, which is instead a level‐specific expansion of the national franchise to include non‐resident citizens and of the local franchise to include non‐citizen residents. This is demonstrated by analysing an original dataset on voting rights in 31 European and 22 American countries, and outlining a level‐sensitive normative theory of citizenship that provides support for this pattern as well as a critical benchmark for current franchise policies. The findings can be summarised in two inductive generalisations: (1) Voting rights today no longer depend on residence at the national level and on citizenship of the respective state at the local level; (2) Voting rights do, however, generally depend on citizenship of the respective state at the national level and on residence at the local level. In the article, these are called the patterns of franchise 'expansion' and 'containment'. The former supports the idea of widespread level‐specific expansion of the franchise and refutes the insular view of the demos . The latter signals corresponding level‐specific restrictions, which defeats over‐generalised versions of deterritorialised or postnational conceptions of the demos . In order to test how robust this finding is, cases are analysed where the dominant patterns of expansion have been resisted and where unexpected expansion has occurred. With regard to the former, the article identifies constitutional and political obstacles to voting rights expansion in particular countries. With regard to the latter, the article shows that even where national voting rights have been extended to non‐citizen residents, containment remains strong through indirect links to citizenship.